Integration of Kaliurang Local Culture into Augmented Reality for Spatial Geometry Learning Media Development - Kufita Rachman; Ilham Rasyid; Ade Puteri Arbiyanti; Siti Raihani Vesya (SAKAGURU: Journal of Pedagogy and Creative Teacher, 2025)
A new challenge in 21st-century learning processes is the demand for technology integration without neglecting the richness of local culture. This research aims to develop Augmented Reality (AR) learning media integrated with the local culture of Kaliurang that is feasible and practical to use. This research approach uses a quantitative and qualitative approach, also known as a mixed method, with a research and development (R&D) design model 4-D consisting of four stages: define, design, develop, and disseminate. Data collection was conducted through interviews and questionnaires. The selection of subjects was carried out through random sampling with a population of sixth-grade students. The sample used in this study consisted of 25 sixth-grade students from SD Negeri Umbulharjo 2 over 2 months. The analysis of interview data was conducted descriptively, while the questionnaire data used descriptive statistical analysis. The analysis results found the need for the development of learning media, which was subsequently assessed for feasibility with an average score of 3.93 or 98.43%, categorized as "Very Feasible" by subject matter experts, and an average score of 4 or 100%, categorized as "Very Feasible" by media experts. The practicality test received an average score of 3.6 or 90%, classified as "Very Practical" by the students. The findings indicate that Augmented Reality (AR) integrated with the local culture of Kaliurang is well used as a learning medium for spatial geometry with the utilization of technology in the classroom at the elementary school level to support the understanding process of students. This research contributes to the development of innovative learning media integrated with the local culture of Kaliurang, which replicates the improvement of mathematics learning quality. Also, it provides a foundation for further research and practical application in the field of education.